A viscosity-sensitive iridium(iii) probe for lysosomal microviscosity quantification and blood viscosity detection in diabetic mice. Issue 12 (6th March 2019) - Zhang, Pingyu; Chen, Haijie; Huang, Huaiyi; Qiu, Kangqiang; Zhang, Changxuan; Chao, Hui; Zhang, Qianling
Abstract : A novel viscosity-sensitive iridium probe enables the detection of cancer and diabetes. Abstract : Abnormal levels of biological viscosity are closely associated with some diseases and malfunction ( e.g. cancer, diabetes). Sensitive viscosity probes are of significant importance in disease diagnosis and remain an unmet need. In this research, we present a novel viscosity-sensitive dinuclear Ir(iii ) complex (1 ), which freely rotates and shows weak phosphorescence in a low-viscosity environment, while in viscous media, both the phosphorescence intensity and lifetime are enhanced significantly.1 can further be applied for phosphorescence lifetime imaging (PLIM) and measure lysosomal microviscosity with high accuracy and reliability. Interestingly, this PLIM property can distinguish between tumorous and nontumorous cells. Importantly, the probe shows much stronger phosphorescence in the fresh blood of diabetic mice than that of normal mice. This work offers a potential efficient probe for diagnosing viscosity related diseases.